Bibliografía española de las Ciencias de la Información (enero - diciembre 1982) - García Gutiérrez, Antonio L.; Martín Martín, Fernando; Valle Gastaminza, Félix del; López Yepes, Alfonso (Documentación de las Ciencias de la Información, 1984)
Sin resumen